Islamic Business Ethics in Buying and Selling Transactions at Pabean Market, Sedati, Sidoarjo - Khayati, Ismatul; Firdaus, Muhammad Fakhri Allam (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Islamic business ethics is a fundamental foundation in shaping economic behavior that is in line with sharia values. This study aims to analyze the application of Islamic business ethics principles in buying and selling transactions at Pabean Market, Sedati, Sidoarjo. The market, initially designed as a tourist market offering Sidoarjo’s local products, has increasingly functioned as a traditional market serving the daily needs of the surrounding community. The research employed a qualitative descriptive approach with a case study design. Informants consisted of five traders and five buyers selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation and member checking. The findings indicate that the implementation of Islamic business ethics in Pabean Market is relatively satisfactory, particularly in the principles of equilibrium, free will, and responsibility. Traders generally sell their products honestly, do not coerce buyers, provide fair services, and are willing to replace defective goods. However, the principles of unity (tauhid) and benevolence (ihsan) have not been fully practiced. This is evident in the inconsistency of some traders in performing obligatory prayers on time and the limited application of benevolence, such as granting credit or showing additional kindness, which tends to be reserved for loyal customers. This study emphasizes the necessity of internalizing Islamic ethical values in every business activity, as they not only strengthen consumer trust and loyalty but also bring spiritual blessings to business actors. Thus, the implementation of Islamic business ethics supports business sustainability while also contributing positively to social welfare and the continuity of the local economy.